Design of liposomes as drug delivery system for therapeutic applications - Guimarães, Diana Isabel Pereira (2021)
Liposomes are spherical vesicles consisting of one or more concentric phospholipid bilayers enclosing an aqueous core. Being both nontoxic and biodegradable, liposomes represent a powerful delivery system for several drugs. They have improved the therapeutic efficacy of drugs through stabilizing compounds, overcoming obstacles to cellular and tissue uptake and increasing drug biodistribution to target sites in vivo, while minimizing systemic toxicity. This review offers an overview of liposomes, thought the exploration of their key fundamentals. Initially, the main design aspects to obtain a successful liposomal formulation were addressed, following the techniques for liposome production and drug loading. Before application, liposomes required an extensive characterization to assurance in vitro and in vivo performance. Thus, several properties to characterize liposomes were explored, such as size, polydispersity index, zeta potential, shape, lamellarity, phase behavior, encapsulation efficiency, and in vitro drug release. Topics related with liposomal functionalization and effective targeting strategies were also addressed, as well as stability and some limitations of liposomes. Finally, this review intends to explore the current market liposomes used as a drug delivery system in different therapeutic applications.